Investigation of the Antibacterial Activity and Antiproliferative Properties of Ag Nanoparticles Synthesized Using Lavandula angustifolia Sevtopolis Extract against Prostate Cancer Cell Lines - Sivri, Firdevs Mert; Akkoc, Senem; Onem, Ebru; Allaberdyyeva, Maysa; Saribas, Rafet (Micro and Nanosystems, 2025)
IntroductionIn this study, silver nanoparticles (AgNPs) were synthesized using Lavandula angustifolia Sevtopolis (LA Sevtapolis) plant extract without using any reducing or stabilizing agent.MethodsThe morphologies, optical properties, and crystallinities of the prepared AgNPs were determined using scanning electron microscopy, UV-visible spectroscopy, and X-ray diffraction.ResultsThe antibacterial activities of the synthesized AgNPs against some gram-negative and gram-positive bacterial species were investigated. The lowest effect was observed against the Gram-positive B. cereus ATCC 11778 with a concentration of 0.0375 µg/mL. Additionally, the toxic effect on the human normal cell line HEK-293T and the antiproliferative activity against the prostate (PC3) cancer cell line were examined. The IC50 values of AgNPs against PC3 and HEK-293T cells were found to be 4.72 µL/mL and 6.838 µL/mL, respectively.ConclusionIn conclusion, due to their antiproliferative and antibacterial activities, AgNPs synthesized using LA Sevtopolis extract were found to have potential applications in various biomedical fields.
Keywords: green chemistry